2021
DOI: 10.1088/1361-6668/abef7d
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting nanostrip single-photon detectors some fundamental aspects in detection mechanism, technology and performance

Abstract: The paper is devoted to several recent rather fundamental achievements in the field of superconducting nanostrip single-photon detectors which make an impact on understanding the detection mechanism, technological challenges and performance metrics important for applications. Special attention is given to static and temporal fluctuations of different origin affecting key metrics of these detectors. Some salient points of older models such as detection criteria or real-time evolution of an electro-thermal domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…From this perspective, it is interesting to understand whether the stoichiometry of Nb x Ti 1−x N could be used for fine-tuning the τ e-ph of the compound. The matter is even more complicated since the superconducting properties of NbN films alone, such as the transition temperature, resistivity, and critical current density, are strongly dependent on the film stoichiometry [13]. It has been shown that SNSPDs based on amorphous superconductors, e.g., silicides such as WSi [14] and MoSi [15], can show favorable properties for the detection of low-energy infrared photons due to their lower superconducting transition temperature compared to Nb-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, it is interesting to understand whether the stoichiometry of Nb x Ti 1−x N could be used for fine-tuning the τ e-ph of the compound. The matter is even more complicated since the superconducting properties of NbN films alone, such as the transition temperature, resistivity, and critical current density, are strongly dependent on the film stoichiometry [13]. It has been shown that SNSPDs based on amorphous superconductors, e.g., silicides such as WSi [14] and MoSi [15], can show favorable properties for the detection of low-energy infrared photons due to their lower superconducting transition temperature compared to Nb-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…During the measurements with all the three wavelengths, the incident photon fluxes were all set to about 1 × 10 6 s −1 . Such a low photon flux on the sensitive area of 15 µm in diameter guarantees the two or more photon response will not happen [40]. PCR is the difference between the total pulse count rate, which is measured with the laser coupled to the fiber, and the system dark count rate, which is measured with the fiber-end at room temperature while the laser was blocked.…”
Section: Fabrication and Experimental Resultsmentioning
confidence: 99%
“…The nonlinear kinetic inductance (given by the factor (I/I ) 2 in equation ( 2)) becomes relevant as larger currents are driven through the traces ( I ). The underlying physics explaining this nonlinearity stems from a perturbative suppression of the superconducting order parameter as the current is increased [40], and consequently the pair density is suppressed, resulting in a quadratic (nonlinear) increase in λ L affecting the prefactor of equation (2). In our devices, typically I 3I c , where I c is the critical current of the traces [41].…”
Section: Theoretical Framework 21 Hki Waveguidesmentioning
confidence: 99%